2016
DOI: 10.7567/apex.9.122402
|View full text |Cite
|
Sign up to set email alerts
|

Fresnoite Ba2TiSi2O8: A novel stimulated Raman scattering active crystal

Abstract: Large Ba2TiSi2O8 crystals were successfully grown by the Czochralski technique. The stimulated Raman scattering properties of the Ba2TiSi2O8 crystals were investigated for the first time, and the first (558 nm) and second (587 nm) Stokes lines were generated in an ultracavity single-pass configuration excited by 532 nm picosecond pulses. The output energy and conversion efficiency of the scattering process as functions of pump energy were studied, and the highest conversion efficiency was found to be 31.8%. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Large-sized Ba 2 TiSi 2 O 8 single crystals with high optical quality were successfully grown from the melt at 1445 • C by the Czochralski method [15,22]. The transmission spectrum, which reflects the linear transmittance and absorbance of the BTS crystal at different wavelengths of light, was measured by an IR-VIS-UV spectrophotometer (Hitachi U-3500, Jasco), using two polished X-cut and Z-cut square wafers with dimensions of 4 × 4 × 1 mm 3 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large-sized Ba 2 TiSi 2 O 8 single crystals with high optical quality were successfully grown from the melt at 1445 • C by the Czochralski method [15,22]. The transmission spectrum, which reflects the linear transmittance and absorbance of the BTS crystal at different wavelengths of light, was measured by an IR-VIS-UV spectrophotometer (Hitachi U-3500, Jasco), using two polished X-cut and Z-cut square wafers with dimensions of 4 × 4 × 1 mm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Haussühl reported that BTS possesses a large electro-optical coefficient, which is of the same order of magnitude as that of KH 2 PO 4 , and so BTS is highly desirable for fabricating devices such as high-speed electro-optic modulators, optical shutters, and laser Q-switches which are used in the fields of laser modulation, optical communications and optoelectronics [10][11][12][13][14]. Furthermore, BTS has proved to be a novel stimulated Raman scattering active crystal, where the Raman gain is slightly greater than that of Ba(NO 3 ) 2 , and hence the crystal is suitable for solid-state Raman laser applications [15].…”
Section: Introductionmentioning
confidence: 99%
“…Fresnoite, Ba 2 TiOSi 2 O 7 , represents a large family of compounds showing diverse properties of piezoelectric, ferroelectric, electro-optical, pyroelectric, and NLO properties. Ba 2 TiOSi 2 O 7 has a NCS P 4 bm tetragonal structure in which the orientation of [TiO 6 ] 8– octahedra with alternating long and short Ti–O bond lengths along the polar c axis produces an intense SHG and a {001} cleavage, and the d 0 Ti 4+ confines the absorption edge to about 300 nm . However, Ba 2 TiOSi 2 O 7 is nonphase-matching (NPM), which puts limitations upon its application.…”
mentioning
confidence: 99%
“…Recently, much attention has been drawn to organic-inorganic hybrid molecular crystals materials [1][2][3][4][5][6][7][8][9][10][11]. These materials are frequently characterized by their various physical and chemical properties, such as structural phase transition, ferroelectric, semiconductor, photovoltaic effect, nonlinear optical response and pyroelectricity, which have potential applications in molecular sensors, switches, data storage, electro optical modulators, light emitting, photo-detector, energy-efficient memories, filtering devices, high-performance insulators and so on [12][13][14][15][16][17][18][19][20][21][22]. Among them, an interesting class is the organic-inorganic hybrid crown type, owing to their large group of structural diversities as well as unique properties (such as dielectric anomaly, ferroelectric, second harmonic generation, nonlinear optical properties, etc.)…”
Section: Introductionmentioning
confidence: 99%